2017
DOI: 10.1371/journal.pone.0175120
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma in high myopia and parapapillary delta zone

Abstract: PurposeTo examine the prevalence of glaucomatous optic neuropathy (GON) in a medium myopic to highly myopic group of patients and its association with parapapillary gamma zone and parapapillary delta zone.MethodsThe retrospective observational hospital-based study included patients who had attended the Tokyo High Myopia Clinics within January 2012 and December 2012 and for whom fundus photographs were available. GON was defined based on the appearance of the optic nerve head on the fundus photographs.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 24 publications
1
53
0
2
Order By: Relevance
“…After adjusting for age, IOP, and AL, their study revealed a significantly smaller radius and greater DA in severe glaucoma which were similar to the corneal deformation responses found in the HM group in our study. Our findings suggest that HM and glaucoma may share some common ocular biomechanical behavior and thus can support the epidemiological findings that show higher prevalence of glaucoma in patients with HM [45,46]. Given that the sclera, cornea, and lamina cribrosa are connected and primarily composed of similar extracellular matrix, corneal biomechanical parameters can be regarded as global properties of the eye [10].…”
Section: Discussionsupporting
confidence: 83%
“…After adjusting for age, IOP, and AL, their study revealed a significantly smaller radius and greater DA in severe glaucoma which were similar to the corneal deformation responses found in the HM group in our study. Our findings suggest that HM and glaucoma may share some common ocular biomechanical behavior and thus can support the epidemiological findings that show higher prevalence of glaucoma in patients with HM [45,46]. Given that the sclera, cornea, and lamina cribrosa are connected and primarily composed of similar extracellular matrix, corneal biomechanical parameters can be regarded as global properties of the eye [10].…”
Section: Discussionsupporting
confidence: 83%
“…Myopic maculopathy and optic nerve atrophy in association with high axial myopia have become some of the most common causes of irreversible vision impairment and blindness 48‐50 . The most important risk factor for the development and progression of myopic maculopathy and highly myopic optic nerve damage is a long axial length and further elongation 51‐53 . If EGF and its family members are involved in the process of axial elongation and if the intraocular application of EGF (family) antibodies reduces further ocular elongation, progression of myopic maculopathy and optic nerve damage may be halted by the intraocular injection of these antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia is a common yet insidious condition, with each dioptre increasing the burden associated with the condition. Particularly, high myopia (≤−5.00D) increases the risk of vision impairment due to complications such as myopic macular degeneration, chorio‐retinal atrophy and glaucoma . Given the substantially high prevalence of myopia in many East Asian countries and rising prevalence elsewhere, its impact on eye health and the associated economic burden is significant …”
Section: Introductionmentioning
confidence: 99%